The Effects of Utilizing the Cooperative Learning Method to Enhance Students’ English Communicative Competence - Nair, Subadrah Madhawa; Yingting, Zhang; Singh, Gurdip Kaur Saminder; Wider, Walton; Siddique, Muhammad (Journal of Ecohumanism, 2024)
Purpose: The study’s first objective was to investigate whether the utilization of the cooperative learning method can enhance Chinese college students’ performance and motivation in English communicative competence. The second objective was to explore students’ views on the cooperative learning method in learning communicative competence. Methodology: This study employed a quasi-experimental design using quantitative and qualitative data. The sample was 80 first-year non-English majors from two polytechnic colleges in Guangdong, China. The Experimental Group and the Control Group, respectively, consisted of 40 students. The Experimental Group was taught using the STAD (cooperative learning) method and the Control Group was taught using the conventional method for eight weeks. Before the intervention, both groups were given a pre-test and after the intervention, they were given a post-test to gauge their performance in English communicative competence. Following that, 8 students from the Experimental Group were interviewed, using semi-structured interview questions to explore their views and experiences on the STAD method. Findings: Results from the post-test indicated that the Experimental Group significantly outperformed the Control Group in their overall score for communicative competence and motivation. Thematic analysis from the focus-group interview showed that the STAD method was a very effective teaching tool in enhancing students’ English communicative competence and facilitated them to improve their fluency and coherence, lexical resource, grammatical range and accuracy, pronunciation, and listening skills. Conclusion: This study has crucial pedagogical implications because it suggests that the STAD method can enhance students’ English communicative competence.